Respuestas
Respuesta dada por:
0
propiedad
![\frac{ x^{m} }{ x^{n} } = x^{m-n} \frac{ x^{m} }{ x^{n} } = x^{m-n}](https://tex.z-dn.net/?f=+%5Cfrac%7B+x%5E%7Bm%7D+%7D%7B+x%5E%7Bn%7D+%7D+%3D+x%5E%7Bm-n%7D+)
quda 36/4=9
![9x^{5-5}* n^{2-1} * p^{10-3} =9x^{0}* n^{1} * p^{7} 9x^{5-5}* n^{2-1} * p^{10-3} =9x^{0}* n^{1} * p^{7}](https://tex.z-dn.net/?f=+9x%5E%7B5-5%7D%2A+n%5E%7B2-1%7D+%2A+p%5E%7B10-3%7D++%3D9x%5E%7B0%7D%2A+n%5E%7B1%7D+%2A+p%5E%7B7%7D++)
quda 36/4=9
Preguntas similares
hace 7 años
hace 7 años
hace 7 años
hace 9 años
hace 9 años
hace 9 años
hace 10 años